Chronicle encyclopedia of history (DK Multimedia, 1997)
Four million years of world history presented through news articles, biographies, themed overviews, video, music, animations, artwork, and pictures. Offers three-dimensional time traveler feature and search and index functions. Includes built-in link to Chronicle Online on the World Wide Web.